Development Gaps in ASEAN as Crucial Security Issues: A Challenge to ASEAN Integration - Basir, Salawati Mat (ASEAN Journal of Legal Studies, 2018)
The ASEAN development gap is the disparity that exists between the ASEAN 6 and CLMV groups. The challenge for ASEAN’s integration isthat the increasingly globalized world and current community-building process of ASEAN could turn the region into the included and the non-include, unless ASEAN can finds appropriate approaches to sustainable bridging the crucial development gaps among itself. Such possibility would threaten the stability of ASEAN from within rather than from outside. This paper provides the discussion on the income gap, the infrastructure gap, trade gap and the institutional gap in order to understand possible outcomes and on what has to be prioritized in the community-building process of ASEAN. Lastly, this paper focuses on regional institution-building and caring far the most vulnerable as the new ASEAN way to bridging the development gaps and for a sustainable ASEAN community in the future.